Perceptions of Foreign Tourists towards Public Transportation Integration with Tourism Destination in the Special Region of Yogyakarta - Fasya, Muhammad Najih (TATALOKA, 2025)
The development of tourism in the Special Region of Yogyakarta (DIY) is still experiencing problems, especially in the aspect of tourism transportation. The main problem is the absence of an adequate transportation management system in the tourism transportation system by integrating supply (tourism transportation) and demand (tourists). Previous studies have only partially explained the integration between modes of transportation and tourism, so there has been no integration between supply (tourism transportation) and demand (tourists) and it is not integrated holistically, especially foreign tourists as respondents. So, this study aims to analyze the effect of public transportation mode integration on the type of tourism and characteristics of foreign tourists. This study uses a quantitative research type using primary data collection techniques carried out by researchers through observation of tourist attractions, interviews with agencies and submitting questionnaires to foreign tourists. In addition, the secondary data source for this study comes from official government documents. The results of the study showed that most foreign tourist respondents in DIY were included in the Mid-centric psychographic characteristics of 92.52%. All respondents were Individual Mass Tourists. From the assessment of integration between public transportation modes in DIY at four DIY transportation nodes, it is also considered good. Although the average integration value reaches 95.31%. Then the results of the statistical test through ordinal regression analysis produced a figure of 22.47%, this percentage is the figure for the influence of public transportation integration on tourist attractions, because most foreign tourists prefer to use vehicle rentals.